Force-based control strategy for a collaborative robotic camera holder in laparoscopic surgery using pivoting motion - Fontúrbel, Carlos; Cisnal, Ana; Fraile-Marinero, Juan Carlos; Pérez-Turiel, Javier (Frontiers in Robotics and AI, 2023)
This paper presents a force-based strategy for the mobility of a robotic camera-holder system for laparoscopic surgery based on a pivoting motion, reconceptualizing the conventional paradigm of the mobility control for these systems, traditionally dependent on a fixed Remote Center of Motion (RCM). Traditional robot control strategies in laparoscopy tend to consider the patient’s abdominal walls as an immobile system, being the RCM a static point of the laparoscopic tool coincident with the patient’s incision, even though this presumption is not so precise in real surgeries, especially in collaborative environments. Although mobile RCMs have been performed in laparoscopic scenarios where trocar-patient contact force is measured, strategies based on other principles are not extended. As opposed to traditional methods, the strategy proposed in this paper in based on the direct control of the Tool Center Point’s (TCP) position and orientation; without position constraint associated with the incision’s spatial position. This method consists of pivoting motions in response of the actual contact between the patient’s abdominal walls and the laparoscope, relating directly force and angular velocity. This reallocates the trocar, whose position becomes a consequence of the natural accommodation allowed because of this pivoting. Therefore, the camera can keep track to any location since the real environment constrains dynamically the orientation of the camera. The proposed motion ensures the safety of the patient’s abdominal walls by minimizing forces caused by undesired or physiological movements of the patient, movements of the laparoscope, or by the tools manipulated by the surgeon during a collaborative procedure. This can be implemented for laparoscopic robots without mechanical RCMs, or commercial collaborative robots, improving the safety of the intervention by the addition of a force/torque sensor.